Strategi Manajemen Pemasaran UMKM dengan Analisis SWOT Guna Meningkatkan Daya Saing pada Toko Sinar Utama di Pekanbaru - Yolanda Citra; Rama Gita Suci; Sarifah Aini Hasibuan; Sollahudin (Jurnal Visi Manajemen, 2025)
This study analyzes the marketing management strategy of UMKM Toko Sinar Utama in Pekanbaru using SWOT analysis. The data used in this study consists of secondary and primary data obtained through interviews, observations, and literature studies. The results of the SWOT analysis show that Toko Sinar Utama has greater strengths and opportunities compared to the weaknesses and threats it faces. Based on the results of the analysis, this study formulates four marketing strategies, namely SO, WO, ST, and WT, which can be applied to increase the competitiveness of Toko Sinar Utama. The SO strategy focuses on optimizing existing strengths and opportunities, the WO strategy aims to overcome weaknesses by utilizing opportunities, the ST strategy utilizes strengths to face threats, and the WT strategy seeks to minimize weaknesses and threats. This study concludes that Toko Sinar Utama has good potential to develop, but needs to overcome existing weaknesses, utilize available opportunities, and anticipate threats that may arise.